Etnološko preučevanje otrok v slovenski etnologiji in folkloristiki - Ramšak, Mojca (Etnolog. Nova vrsta (Ljubljana), 2007)
The ethnological study of children includes the cultural appreciation and conception of childhood, the cultural aspects of children's development, growing up and socialisation, the levels of material and spiritual satisfaction of children's needs, and their different positions in communities. Further subjects of the ethnological study of children are live performances of children's folklore in concrete environments, including their function and aesthetics as they are determined by children's imagination and the contemporary social, family, and material conditions. The subject of theoretically founded folkloristics is research into children's folklore as childrenćs creative role in the artistic and social culture of children and adolescents.
Keywords: Slovenci; Slovenes; ethnology; etnologija; folkloristics; folkloristika; child; otroci; igre; igrače